Visual paradox as a means of visual semantic foregrounding - Lahiani, Hanene; Alghazali, Fawzi; Abouelnour, Moustafa Mohamed; Al Mahamed, Ahmad Mohammad; Abou Adel, Mohammed A. (Research Journal in Advanced Humanities, 2026)
This study explores the role of visual paradox as a stylistic device for achieving semantic foregrounding in advertising imagery, addressing an overlooked gap in research on visual semiotics. It focuses on how paradox shapes meaning and enhances communicative impact within multimodal contexts. The study investigates two selected advertisements—Seiko Lassale and Nestlé Munch Bunch—and adopts a triangulated qualitative approach that integrates semiotic-stylistic analysis, audience reception through a questionnaire involving 30 university students, and expert interviews with specialists in visual communication and cognitive semiotics. The findings demonstrate that paradox, created through techniques such as spatial disruption, role reversal, and unexpected visual juxtapositions, provokes psychological defamiliarization, captures the viewer’s attention, and stimulates deeper interpretive engagement. Key visual strategies, including compositional structure, contrasts in lighting, nuanced color blending, and the application of linear perspective via the Ponzo illusion, are shown to be essential in generating paradoxical effects. The study argues that paradox should not be viewed merely as an aesthetic ornament but as an intentional cognitive and persuasive strategy that reinforces the communicative strength of advertising images. It further highlights their stylistic and psychological dimensions, showing how paradox simultaneously activates cognitive processing and emotional response, thereby enhancing both the memorability and persuasive power of advertising discourse. Ultimately, the study offers a fresh contribution to multimodal stylistics and visual semiotics by positioning paradox as a central tool for semantic foregrounding in contemporary advertising.